Disquieted by Online Hate: Negative Experiences of Finnish Adolescents and Young Adults - Savimäki, Tuukka (European journal on criminal policy and research, 2020)
Online hate is becoming a growing public concern, but so far, the phenomenon has not been studied from the perspective of fear of crime. This study examined why some people are disquieted more by hateful online content than others. The data consist of Finnish participants (n = 1726) between 15 and 30 years old. The main analysis focused on participants who had seen online hate content during the past 3 months. The feeling of being disturbed by this type of material is, in this article, operationalized with the concept of disquiet referring to a feeling of anxiety or uneasiness. The findings, based on ordinary least-squares regression analysis (OLS), show that the intensity of such negative experiences was stronger for women, immigrants, and those who had faced previous online and offline victimization. Risk-takers were less likely to be disquieted by online hate. In addition, those worrying about becoming online hate victims were more disquieted by online hate than others. The findings emphasize that online hate content may have a strong impact on those who are already in a vulnerable position. Overall, the study supports the idea that online and offline worlds are not two separate realities but rather coexisting dimensions of one social sphere.